Preventing other ‘Marawis’ in the southern Philippines - Franco, Joseph (2019)
After more than 5 months of intense fighting, the Battle for Marawi has concluded as the largest urban combat scenario in modern Philippine history. Winning a kinetic campaign against violent extremist organisations like the Maute Group is insufficient in itself to prevent the eruption of other ‘Marawis’ in the future. The Duterte Administration should craft a cohesive countering violent extremism strategy. A prospective strategy should recognise the importance of coherent messaging and focus on the non‐ideological drivers of conflict.